Implementasi Pembelajaran IPA Berbasis Project Terhadap Kemampuan Berpikir Kritis Siswa Kelas V Sekolah Dasar Islam Terpadu - Putri Rahayu Pertiwi; Retno Triwoelandari; Muhammad Faishal Hidayat (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the effectiveness of project-based learning (PBL) in science education to enhance the critical thinking skills of fifth-grade students at SDIT Qurrata'aini Baitussalam. Using a Mixed Methods approach with a Sequential Explanatory design, the results indicate that the Project-Based Learning (PBL) model has a significant impact on the development of students' critical thinking skills. Quantitative analysis using the Independent Samples T-Test shows a significance value of 0.000 (< 0.05), indicating a substantial improvement in students' critical thinking abilities after implementing PBL. Observations and interviews with teachers reveal that students involved in projects are more engaged in discussions, able to formulate hypotheses independently, and more critical in evaluating information. Despite challenges such as limited facilities and time constraints, student enthusiasm and strong support from both the school and parents serve as the primary factors contributing to the success of this method. The findings of this study have implications for the education sector, including the need to enhance learning facilities, adjust the curriculum to allow more flexible time allocation for projects, and strengthen collaboration between schools and parents to support students' scientific exploration. With optimal PBL implementation, science education at the elementary school level can become more innovative and effective in fostering students' critical thinking skills.